Implementasi Layanan Bimbingan Konseling Berbasis Pendidikan Ramah Anak Di SD Muhammadiyah 16 Surakarta - Pratiwi, Roeyani Lis; , Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
Implementation of guidance and counseling services need to pay attention to the rights, needs and adjusted by the development of students. This study aims to determine the implementation of guidance counseling education-based child-friendly in SD Muhammadiyah 16 Surakarta, to find out the obstacles of implementation of guidance counseling education-based child-friendly in SD Muhammadiyah 16 Surakarta, and the solution of obstacles to the implementation of guidance counseling education-based child-friendly in SD Muhammadiyah 16 Surakarta. This study uses qualitative research, with phenomenological research design. The results showed that (1) classroom teachers implement guidance and counseling services based child-friendly education well by looking at the appropriateness of the type of guidance counseling and principles of child-friendly education; (2) obstacles to the implementation of counseling services based child-friendly education to occur in some types of counseling services and the implementation of child-friendly education; (3) the solution of constraints given by the class teacher and the principal.